The Influence of The Jigsaw Learning Model on Critical Thinking Skills - Muliawan, Wawan (Universitas Sebelas Maret, 2023)
This study aimed to investigate the impact of using the Jigsaw Type Learning Model on the Critical Thinking Ability of Class XI students at a certain high school. The research followed an experimental approach using Quasi-Experimental Design. The population in this study consisted of two classes, with a total of 76 students in the first semester of Class XI IPA. A simple random sampling technique was used to select Class XI IPA 2 as the experimental group and Class XI IPA 1 as the control group. The critical thinking ability test in the form of an essay test, consisting of 10 questions, was used as the research instrument. The results of the data analysis showed that the average post-test score for the experimental group was 83.59, while the control group's average post-test score was 50.08. Based on the statistical analysis using the t-test formula with a 5% confidence level, the calculated t-value was 15.7. When compared with the t-table value of 1.404, it was found that t-value of 15.7 > t-table value of 1.404. Therefore, the conclusion drawn from this study was that there is a significant impact of using the Jigsaw Type Cooperative Learning Model on the Critical Thinking Ability of Class XI Students at the mentioned high school